Neem Leaf Extracts and Azadirachtin Trigger a Moderate Early Defense Response in Sunflowers Infected with Downy Mildew Caused by Plasmopara halstedii (Farl.) Berl. et de Toni - Rita Bán; Pratik Doshi; Arbnora Berisha; Katalin Körösi; József Kiss; György Turóczi; Božena Šerá; András Skornyik; Nisha Nisha (Agriculture)
This study examined the effectiveness of neem leaf extract (NLE) and azadirachtin (AZA) against two isolates of Plasmopara halstedii, which causes downy mildew in sunflowers. We also explored their physiological and histopathological effects. The pre-inoculation treatments included 10% and 20% NLE and 0.01% and 0.1% AZA, compared to a mefenoxam-treated control and a non-treated control. All treatments significantly reduced the disease rate compared to the inoculated controls (which had a 73–76% disease rate). The 10% NLE treatment showed the strongest effect against isolate 1 (0% damping-off), while the 20% NLE treatment was most effective against isolate 2 (4% damping-off). Neem treatments also significantly improved plant height; for instance, 20% of NLE-treated plants inoculated with isolate 2 reached approximately 15 cm, compared to about 8 cm in the inoculated controls. Histological analyses indicated limited hyphal spread and low levels of cortical necrosis in neem-treated plants, particularly with 0.1% AZA treatment. This suggests a moderate initial defense response without extensive hypersensitive cell death. Neem treatments were comparable to mefenoxam treatments. These results highlight the potential of neem-derived products, particularly 10% NLE and 0.1% AZA, for the integrated management of sunflower downy mildew through both direct pathogen suppression and enhanced host resistance.